(untitled) (American Journal of Research in Humanities and Social Sciences, 2022)
This article talks about the biography of one of the famous personalities, a powerful scientist, a philosopher, a good doctor, a connoisseur of the science of logic and astronomy and a poet of the 12th century Ashrafi Samarkandi. In particular, the name, surname, environment and literary activity of the poet are investigated in the article.